Natural gas pyrolysis in the melt of sodium chlorides - Тарасов, Вадим Юрьевич (Eastern-European Journal of Enterprise Technologies, 2012)
Hydrogen is the main component for nitrogen fertilizers production, hydrogenation processes of oil products and other reagents in organic, inorganic, and metallurgical production. The only large-capacity process in the industry is a multistage catalytic vaporous conversion of natural gas. It is possible to reduce raw materials, energy, capital expenditures, and to solve environmental problems of hydrogen production, if only the ideology of raw materials processing is changed. The article is devoted to the natural gas pyrolysis and its energy supply of the oxidation of formed carbon in the liquid coolant that will justify a new one-stage production technology of hydrogen. The influence of the switchgear on the model and the working fluid was studied. The melt of sodium chloride was chosen as a coolant. The impact of resistance of the dry disperse device is defined by the dependence of the net section from the amount of natural gas. At temperature of coolant 1233 K the change of diameter of the collimator port of the pipe from 1 to 5mm increases the concentration of hydrogen in gaseous products of the reaction 1.2 - 1.8 times. Increase of gas positive pressure of the system over the range 50 to 7000 Pa, reduces the hydrogen content 2.2 times. The increase of the working surface of the disperse device showed that mutual overlap of reaction zones and the interaction of the jet with the waves of the melt, caused by the operation of adjacent point of entry, are present.